Strongly basic anion exchanger Lewatit MonoPlus SR-7 for acid, reactive, and direct dyes removal from wastewaters. Issue 7 (3rd May 2018) - Wawrzkiewicz, Monika; Hubicki, Zbigniew; Polska-Adach, Ewelina
ABSTRACT: The strongly basic anion exchanger Lewatit MonoPlus SR-7 (SR-7) of polystyrene matrix was applied for removal of the textile dyes such as C.I. Acid Orange 7 (AO7), C.I. Reactive Black 5 (RB5), and C.I. Direct Blue 71 (DB71). The dyes sorption on SR-7 was examined based on the initial dye concentration, phase contact time, type of additives and their concentrations, and solution pH. The equilibrium and kinetic characteristics of the dyes uptake by SR-7 followed the Langmuir isotherm model and the pseudo-second-order model. The dyes sorption in the column system was also investigated.